Relationship Between Systemic Inflammation and Glycemic Control in Firefighters - Tiffany J. Oberther; Andrew R. Moore; Austin A. Kohler; A. Maleah Holland-Winkler (Journal of Functional Morphology and Kinesiology, 2025)
Background: Firefighters are at risk for developing metabolic diseases such as type 2 diabetes due to occupational-related stress and poor health behaviors. Firefighters often experience chronic inflammatory responses that may contribute to the development of insulin resistance. This study examined the relationship between systemic inflammation markers and glycemic control markers in firefighters. Methods: Blood samples were collected from twenty full-time male firefighters to assess HbA1c, fasting glucose, and insulin to estimate the Homeostatic Model of Assessment of Insulin Resistance (HOMA-IR), C-reactive protein (CRP), and homocysteine. Body composition and cardiovascular metrics were also recorded. Pearson partial correlation analyses were performed to evaluate relationships between homocysteine and CRP and the variables HOMA-IR and HbA1c while controlling for age and body fat percentage (BF%). SPSS version 29 was used for all analyses (α = 0.05). Data transformation was used where appropriate to ensure the normal distribution of each variable. Results: A significant positive correlation was found between homocysteine and HbA1c before (p = 0.006, r = 0.605) and after controlling for age and BF% (ppartial = 0.013, rpartial = 0.588), indicating that homocysteine levels are associated with impaired glycemic control in firefighters. No other relationships were found to be significant. Conclusions: The findings support a potential link between systemic inflammation and poor glycemic control in firefighters. Due to the occupational hazards that contribute to chronic inflammation, targeted interventions such as dietary modifications may help decrease the risk of diabetes and cardiovascular disease in this high-risk population.